2022
DOI: 10.1038/s41388-022-02264-3
|View full text |Cite
|
Sign up to set email alerts
|

The proteomic characterization of the peritumor microenvironment in human hepatocellular carcinoma

Abstract: The tumor microenvironment (TME) was usually studied in tumor tissue and in relation to only tumor progression, with little involved in occurrence, recurrence and metastasis of tumor. Thus, a new concept “peritumor microenvironment (PME)” was proposed in the proteomic characterization of peritumor liver tissues in human hepatocellular carcinoma (HCC). The PME for occurrence (PME-O) and progression (PME-P) were almost totally different at proteome composition and function. Proteins for occurrence and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Although targeted molecular therapies and immunotherapy have demonstrated encouraging treatment benefits for HCC patients recently, and atezolizumab and bevacizumab are used as first-line treatment for advanced HCC [ 42 ], the overall clinical prognosis of HCC patients are far from satisfactory as a consequence of drug resistance [ 1 , 4 ]. Many studies were performed to explore effective models to precisely predict the prognosis and response to treatment of HCC patients, in the hope of providing more evidence for precision therapy [ 43 , 44 , 45 ]. Therefore, it is imperative to detect novel validated prognostic biomarkers and construct new models to predict the precise treatment for HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although targeted molecular therapies and immunotherapy have demonstrated encouraging treatment benefits for HCC patients recently, and atezolizumab and bevacizumab are used as first-line treatment for advanced HCC [ 42 ], the overall clinical prognosis of HCC patients are far from satisfactory as a consequence of drug resistance [ 1 , 4 ]. Many studies were performed to explore effective models to precisely predict the prognosis and response to treatment of HCC patients, in the hope of providing more evidence for precision therapy [ 43 , 44 , 45 ]. Therefore, it is imperative to detect novel validated prognostic biomarkers and construct new models to predict the precise treatment for HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although phosphopeptides, ordinary tryptic peptides, metabolites, and lipids are all detected by LC-MS/MS, at a practical level, phosphoproteomics is considerably more complex and challenging to implement for clinical samples than other omics. Previous studies have identified over 20,000 phosphopeptides or phosphorylation sites in HCC tumors using high-pH reverse phase fractionation (one sample, six injections) and TiO2 enrichment [23][24][25][26][27][28][29][30][31][32][33][34]. Taking advantage of the high sensitivity and speed of the timsTOF Pro 2 mass spectrometer and the complementary results of IMAC Fe-NTA and TiO2 profiling [45][46][47], a comparable number of phosphopeptides has been obtained using a much simpler approach (one sample, two injections; routine DDA data acquisition without projectspecific proteomics libraries).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogeneity of tumor tissue, omic studies in this research could not identify specific cell types. Although this limitation might be partially addressed by bioinformatic assays [25], elaborate biological experiments are needed for validation. Additionally, glycogen synthase kinase 3α (GSK3A) was hyperactivated in advanced-stage HCC, which is responsible for glycogen accumulation and tumorigenesis by the suppression of Hippo signaling through glycogen-induced phase separation [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu et al proposed a new concept of the peritumor microenvironment (PME) and explored the proteomic characterization of the PME for occurrence (PME-O) and progression (PME-P) in human hepatocellular carcinoma (HCC) [45]. Immunity was found essential in PME-O, while inflammation, angiogenesis, and metabolism were critical in PME-P. Proteome profiling identified thymidine phosphorylase (TYMP) as an antiangiogenic target in the HCC mouse model.…”
Section: Proteomicsmentioning
confidence: 99%